Antioxidant properties of selected Etlingera and Zingiber Species (Zingiberaceae) from Borneo Island - Sabli, F.; Mohamed, M.; Rahmat, A.; Ibrahim, H.; Abu Bakar, M.F. (Academic Journals, New York, 2012)
In this study, total phenolic and flavonoid contents as well as antioxidant properties of methanolic extracts of rhizomes and stems of four Zingiberaceae (Etlingera belalongensis, Etlingera velutina, Zingiber vinosum and Zingiber pseudopungens) were investigated. Evaluation of antioxidant activity was conducted using 1,1-diphenyl-2-picrylhydrazyl free radical-scavenging (DPPH) assay, 2-2-azinobis-3-ethylbenzothioazaline-6-sulphonate radical scavenging (ABTS) assay and Ferric-Reducing Antioxidant Power (FRAP). The results showed the total phenolic and total flavanoid contents were in the range of 5.3-41.7 mg gallic acid equivalent/g and 1.09-5.86 mg catechin equivalent/g of dry sample, respectively. The antioxidant activities of the extracts as assessed by using DPPH and FRAP assays were strongly correlated with all phytochemical tested (p<0.05). As a conclusion, selected tropical gingers found in Sabah investigated in this study can be developed as natural antioxidant agents.